Developmental constraints do not influence long-term phenotypic evolution of marsupial forelimbs as revealed by interspecific disparity and integration patterns. - Martín-Serra, Alberto; Benson, Roger B.J. (The University of Chicago Press, 2020)
Marsupials show a smaller range of forelimb ecomorphologies than placental mammals, and it is hypothesized that this results from macroevolutionary constraints imposed by the specialized reproductive biology of marsupials. Specifically, the accelerated development of the marsupial forelimb allows neonates to crawl to the mother’s pouch but may constrain adult morphology. This hypothesis makes three main predictions: (i) that marsupial forelimbs should show less interspecific disparity than their hindlimbs, (ii) that morphological integration within the marsupial forelimb is stronger than integration between limbs, and (iii) that these patterns should be strongest in diprotodontians, which undergo the most rigorous crawls as neonates. We use a three-dimensional geometric morphometric data set of limb bones for 51 marsupial species to test these predictions. We find that (i) marsupial forelimbs and hindlimbs show similar disparities, (ii) no clear differences in integration exist either within or between limbs, and (iii) the same patterns occur in diprotodontians as in other marsupials, even correcting for lineage age. Therefore, there is currently little evidence that the developmental biology of marsupials has constrained their macroevolutionary patterns. It is possible that functional selection can overcome the effects of developmental constraint on macroevolutionary timescales. Our findings suggest that the role of developmental constraints in explaining the limited phenotypic variability of marsupials (compared with that of placentals) should be reconsidered
Política de acceso abierto tomada de: https://www.journals.uchicago.edu/open
Keywords: Marsupiales - Evolución; Marsupiales - Morfología; Marsupials; Constraints; Integration; Disparity; Geometric morphometrics